Adventure Tourism - Buckley, Ralf (CABI, 2014)
Adventure tour operations change continually, and certainly faster than any one author can keep checking them. Information in the case studies and elsewhere in this volume has been compiled from a variety of written and electronic documents, and personal observations and experiences, which themselves date from different years or even decades. Where possible, publicly available statistical information has been updated during 2005 from tour operator websites and similar sources. These sources, however, may be outdated or inaccurate and no guarantees are expressed or implied regarding any such data.